(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
Rice is a major staple food in Vietnam in which brown rice has been recognized as a potential feedstuff for poultry but data on nutritional value of this feed are lacking. In this study the using of brown rice as replacement of corn in chicken diet was evaluated. The body weight, feed intake and feed conversion ratio were recorded. In total, 192 day old chicks of country breed (Ri lai) were used in this study. Chickens were divided into four groups and reared at same conditions for 12 weeks. The first group as the control group fed on 100% corn, second group fed on 75% corn and 25% brown rice, third group fed on 50% corn and 50% brown rice and the last group fed on 25% corn and 75% brown rice. The average body weight of chickens among all the treatments was 1.7 kg per bird which was not significantly different (P=0.44). The total feed intake of chickens (4-5 kg) was recorded without significant difference (P=0.23), however the feed conversion ratio were significantly different (P<0.05) between treatments. This study considered as the first report that demonstrates the usefulness of brown rice as a potential alternative of corn for chicken diet in rural areas in Vietnam, especially on the prevailing conditions such as during high price spell of corn. Res. Agric., Livest. Fish.3(1): 139-144, April 2016